Evaluasi Program Pembelajaran on the Job Training di Lembaga Pendidikan Vokasi - Rahmat Dwi Sanjaya; Iis Prasetyo; Ahmad Rossydi (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2022)
The research objective to evaluate the On-the-Job-Training (OJT) program organized by Vocational Higher Education with a particular emphasis on the Air Traffic Controller (ATC) Study Program at Aviation Polytechnic of Makassar. The evaluation has three parts: design, implementation, and learning program outcomes. The research was conducted with a qualitative approach and used the descriptive analysis method. The data were collected through observation, interviews, and documentation by the On the Job Training Instructor (OJTI), the ATC Study Program, and OJT Participants. The results of this study, were: (1) The evaluation of learning-program design asserted that the competency plan to be developed, the learning strategy, and the learning program were by the competency needs and the Graduate Learning Outcomes of the ATC Study Program (2) The evaluation of the learning program's implementation indicated that the program's implementation, which includes the implementation of learning activities, the implementation of learning by OJTI and OJT Participants, and the interaction patterns established during the program, were all in line with the prepared plan. (3) The evaluation of learning program outcomes indicated that the results of the learning program were as planned, and the OJT program had a positive impact on the cadets. Nevertheless, in terms of achieving objectives, the OJT program still needs redevelopment to execute the program objectives.